Identification of residual ischemia in the occluded coronary artery irrigation area using myocardial perfusion scintigraphy - Baškot Branislav; Obradović Slobodan; Gligić Branko; Rafajlovski Sašo; Marković Ljuba; Pavlović Miodrag (Vojnosanitetski Pregled)
Background. Inspite the indisputable significance of coronarography, the implications of a revealed stenosis - and how close it is to occlusion could vary in regard to its physiological importance. Myocardial perfusion scintigraphy (MPS) possibility to prove and objectivise the presence of ischemia and myocardial viability within an occlusion found coronarographically is especially significant since it makes possible to the clinician to choose an adequate therapy. Case report. We reported a 43- year-old male patient who had been hospitalized to another institution due to acute myocardial infarction (AMI) of posterolateral localisation. Following the acute AMI stage the ergometric test per Bruce protocole was performed, negative to ischemic heart disease, while multislice computed tomography showed no significant changes on the coronary arteries. The performed one-day-protocole MPS showed a massive area of residual ischemia within myocardial infarction (MI) type culprit lesion of the posterolateral zone starting from the subapical level to the basal cross-section. According to the MPS findings coronarography was indicated due to a revascularisation assessment. The performed coronarography revealed an occlusion of the circumflex coronary artery (CCA) right after the division of obtuse branch (OB) that presented discretely in the distal parts from the homo- and heterocolaterals. The distal portion of CCA presented discretely out off the right coronary artery (RCA). Echocardiography confirmed an ejection fraction of 50% with hypokinesia of inferior and posterior walls, as well as the septum, showing a mild reduction of the general contractility. Flows through confluences were well. A month after MI a percutane coronary intervention (PCI) was performed with the implantation of a drug-releasing stent (Taxus). Early after PCI (within two weeks) a control MPS was done to evaluate the effects of the therapy giving the normal findings of myocardial perfusion. Conclusion. Determination and identificantion of vivid but ischemic myocard of culprit lesion type in the occluded artery irrigation zone enable making choice of the best therapy for a patient.